Răspuns :
(2x +2y) +(3x + 3y)² + (4x+4y) ³ =
2(x + y) + (3(x + y))² + (4(x + y))³ =
2 (x + y) + 9(x + y)² + 64 (x + y)³ =
2 × 1 + 9 × 1² + 64 × 1³ =
2 + 9 + 64 =
11 + 64 =
75
2(x + y) + (3(x + y))² + (4(x + y))³ =
2 (x + y) + 9(x + y)² + 64 (x + y)³ =
2 × 1 + 9 × 1² + 64 × 1³ =
2 + 9 + 64 =
11 + 64 =
75
A)
= 2(x+y) + [3(x+y)]^2 + [4(x+y)]^3
= 2x1+ (3x1)^2+(4x1)^3=
=> 2+ 9+64=
=> 75
Sper ca te-am ajutat !
= 2(x+y) + [3(x+y)]^2 + [4(x+y)]^3
= 2x1+ (3x1)^2+(4x1)^3=
=> 2+ 9+64=
=> 75
Sper ca te-am ajutat !